COVID-19 lockdown as an opportunity to rethink urban freight distribution: Lessons from the Barcelona metropolitan area. (June 2022) - Castillo, C.; Viu-Roig, M.; Alvarez-Palau, E.J.
Highlights: Daily operations of logistics companies temporarily benefited from lockdown. Due to COVID-19 uncertainty, UFD operations varied widely depending on the sector. The rise in ecommerce deliveries resulted in adjustments to the distribution models. Barcelona city council used lockdown to prioritise non-motorised transport modes. To improve UFD efficiency, dialogue between stakeholders must be fostered. Abstract: The COVID-19 health crisis has had a strong impact on societies around the world, affecting both the health of populations and countries' economies. While lockdowns imposed to stop the spread of infection reduced urban mobility and had a positive impact on air quality, lowering the emission of polluting particles and greenhouse gases, they had the opposite effect on urban freight distribution (UFD). With the population remaining at home, ecommerce-driven shipments surged, and total freight traffic increased. In order to have a better understanding of this phenomenon, the aim of this study was to identify the impact of COVID-19 lockdowns on the daily operation of the region's main logistics agents. Lessons learned from this cyclical scenario could be used to define more sustainable public policies regarding UFD in the post-COVID era. To meet the above objectives, semi-structured interviews were conducted with public administrations and private operators, before being transcribed and encoded for later analysis. The results of our study show that common problems in UFD, such as traffic congestion or problems finding parking in the loading and unloading (L/U) zones, temporarily disappeared during the lockdown phase. Delivery times were consequently reduced, despite an increase in operations due to ecommerce. In addition, the public administrations took advantage of this situation to adapt the urban space and force a transition towards new delivery systems, such as cargo-bikes, to guarantee sustainable last-mile operations in specific zones.